Application status of holmium and thulium fiber laser for urological calculi - Hou, Shu-Ping; Wang, Yu-Guo (Frontiers in Physics, 2025)
Holmium:YAG(Ho:YAG) is still recognized as the gold standard for lithotripsy due to its advantages of high efficiency, safety, wide indications and high compatibility with minimally invasive techniques. However, it still faces challenges such as calculi retropulsion and heat generation risk in clinical applications. With its unique structure and physical properties, thulium fiber laser (TFL) boasts advantages such as higher performance efficiency, superior stability, and an increased energy conversion rate. These features endow TFL with broad application prospects in the treatment for urological calculi, and it is anticipated to become for calculi fragmentation in the future. This article will analyze the performance characteristics of Ho:YAG and TFL, and explore their characteristics and advantages in urolithiasis surgery, in order to provide guidance and inspiration for clinical practice.